Imaging of nerve injury in neonatal acute bilirubin encephalopathy using 1H-MRS and Glu-CEST techniques - Lin, Qihuan; Chen, Lanmei; Zheng, Hongyi; Tan, Hui; Zhang, Gengbiao; Zheng, Wenbin (Frontiers in Neuroscience, 2023)
Objectives: To investigate the significance of proton magnetic resonance spectroscopy (1H-MRS) and glutamate chemical exchange saturation transfer (Glu-CEST) techniques in assessing the condition and prognosis of acute bilirubin encephalopathy patients and to understand the mechanism of nerve injury in this disease. Methods: From September 2019 to February 2021, 31 neonates with acute bilirubin encephalopathy and 16 healthy neonates were enrolled in this study. All the quantitative results of 1H-MRS, Glu-CEST, and conventional magnetic resonance imaging (MRI) of all neonates were analyzed. The association between indicators of the Gesell Developmental Schedules and developmental quotients (DQ) was analyzed. Results: The 31 cases were assigned to the mild subgroup (n = 21) and moderate and severe subgroup (n = 10) according to the bilirubin-induced neurologic dysfunction (BIND) scores. The case group had elevated Cho and GABA absolute concentrations compared to the normal control group (all p < 0.05). Compared with the normal control group, the absolute concentration of GABA of the moderate and severe subgroup was significantly larger (p < 0.05). Compared with the normal control group, the Glu-CEST% values in the left basal ganglia, right thalamus, left frontal cortex and bilateral medial geniculate body of the case group was significantly larger (all p < 0.05). The moderate and severe subgroup had higher Glu-CEST% values in the left basal ganglia, right thalamus, and bilateral medial geniculate body than the normal control group (all p < 0.05). A negative association was revealed between the DQ scores and the Glu-CEST% values in the left basal ganglia (r = -0.888, p < 0.05). Conclusion: The combination of 1H-MRS and Glu-CEST techniques can monitor the intracerebral metabolite level of acute bilirubin encephalopathy and evaluate the illness severity. Keywords: acute bilirubin encephalopathy, proton magnetic resonance spectroscopy, glutamate chemical exchange saturation transfer, brain,nerve injury